2010
DOI: 10.1068/p6752
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Laughing in Your Face: Influences of Visual Laughter on Auditory Laughter Perception

Abstract: Hearing the sound of laughter is important for social communication, but processes contributing to the audibility of laughter remain to be determined. Production of laughter resembles production of speech in that both involve visible facial movements accompanying socially significant auditory signals. However, while it is known that speech is more audible when the facial movements producing the speech sound can be seen, similar visual enhancement of the audibility of laughter remains unknown. To address this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…For example, a beard may occlude much of the lower face, and the relevance of other facial areas (e.g., upper jaw/upper cheeks) may become greater than for other talkers. Moreover, speech may not be the only facial signal to tolerate substantial occlusion during social interaction, since the audibility of other socially significant facial signals, such as laughter, is also affected by seeing facial movement (Jordan & Abedipour, 2010). Indeed, laughter is often regarded as an evolutionary precursor to speech (e.g., Darwin, 1872;Niemitz, Loi, & Landerer, 2000;Provine, 2004), which may suggest that the tolerance of facial occlusion shown by speech perception has its origins at an evolutionarily earlier stage of human social communication that adapted to the demands of bimodal speech perception that eventually evolved.…”
mentioning
confidence: 99%
“…For example, a beard may occlude much of the lower face, and the relevance of other facial areas (e.g., upper jaw/upper cheeks) may become greater than for other talkers. Moreover, speech may not be the only facial signal to tolerate substantial occlusion during social interaction, since the audibility of other socially significant facial signals, such as laughter, is also affected by seeing facial movement (Jordan & Abedipour, 2010). Indeed, laughter is often regarded as an evolutionary precursor to speech (e.g., Darwin, 1872;Niemitz, Loi, & Landerer, 2000;Provine, 2004), which may suggest that the tolerance of facial occlusion shown by speech perception has its origins at an evolutionarily earlier stage of human social communication that adapted to the demands of bimodal speech perception that eventually evolved.…”
mentioning
confidence: 99%
“…As supported by Equation (1), participants that experienced the lightscape in this condition showed weak sensitivity to soundscape perception. Equation (2) suggests that a perceived lightscape may enhance the perceived soundscape when eyes are open in the first condition, because perceived lightscape sensitivity may occupy the main cognitive resources, while the perceived soundscape may be a subsidiary cognition for the perceived lightscape, like a sense of background sound for visual perception [69]. The second condition, where L Aeq,5min variations were more than 1.24 dBA, was mostly in the morning and dusk, with active biophonies (e.g., birdsongs) present [16,70].…”
Section: Relationship Between the Sensitivity Of Perceived Soundscape And Lightscapementioning
confidence: 99%
“…It has been shown that speech and laughter become more intelligible, especially under noisy conditions, for humans when visual information is present [11], [12]. This finding has inspired research on audiovisual speech and emotion recognition.…”
Section: Introductionmentioning
confidence: 99%